Dynamics and extreme plasticity of metallic microparticles in supersonic collisions - Wanting Xie (Scientific Reports, 2017)
Abstract Metallic microparticles can acquire remarkable nanoscale morphologies after experiencing high velocity collisions, but materials science regarding the extreme events has been limited due to a lack of controlled experiments. In this work, collision dynamics and nonlinear material characteristics of aluminum microparticles are investigated through precise single particle collisions with two distinctive substrates, sapphire and aluminum, across a broad range of collision velocities, from 50 to 1,100 m/s. An empirical constitutive model is calibrated based on the experimental results, and is used to investigate the mechanics of particle deformation history. Real-time and post-impact characterizations, as well as model based simulations, show that significant material flow occurs during the impact, especially with the sapphire substrate. A material instability stemming from plasticity-induced heating is identified. The presented methodology, based on the use of controlled single particle impact data and constitutive models, provides an innovative approach for the prediction of extreme material behavior.